2015
DOI: 10.1080/13607863.2015.1078279
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for living, meaning in life, and suicide ideation: investigating the roles of key positive psychological factors in reducing suicide risk in community-residing older adults

Abstract: These findings add to a growing body of literature suggesting merit in investigating positive psychological factors together with negative factors when assessing suicide risk and planning psychological services for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 71 publications
5
48
2
Order By: Relevance
“…Meaning in life also was a partial mediator between gratitude, grit, and suicidal ideation in students [20], partially explaining the buffering effect of these constructs on suicidal thoughts. Meaning in life was also a mediator between reasons for living and suicidal ideation in older adults from a community sample [21], which decreases the likelihood of contemplating suicide. In a more recent study, meaning in life, conceptualized as a sense of coherence, was also found to be a moderator between emotion-oriented coping, avoidancedistraction coping, and suicidal manifestations in students, especially in females [22].…”
Section: Meaning In Life and A Search For Itmentioning
confidence: 97%
“…Meaning in life also was a partial mediator between gratitude, grit, and suicidal ideation in students [20], partially explaining the buffering effect of these constructs on suicidal thoughts. Meaning in life was also a mediator between reasons for living and suicidal ideation in older adults from a community sample [21], which decreases the likelihood of contemplating suicide. In a more recent study, meaning in life, conceptualized as a sense of coherence, was also found to be a moderator between emotion-oriented coping, avoidancedistraction coping, and suicidal manifestations in students, especially in females [22].…”
Section: Meaning In Life and A Search For Itmentioning
confidence: 97%
“…Among the variables related to suicide risk, previous studies have highlighted the importance of individual unrest, 38 personal satisfaction, 39 and reasons for living, particularly those related to beliefs in one's own capacities and abilities to cope with situations. 40,41 The presence of certain variables during evaluation (such as personal satisfaction and reasons for living) when someone is thinking about killing oneself can represent focal points that healthcare professionals may attend to when treating patients with suicidal behavior. In other words, promoting analysis of these factors during treatment may assist in distancing patients from emotional and cognitive states that keep them at risk of suicide.…”
Section: 2mentioning
confidence: 99%
“…Bakhiyi, Calati, Guillaume, and Courtet () found via a review of 39 studies that high scores on the Reasons for Living inventory (Linehan et al, ) correlated with lower levels of suicidal ideation and fewer suicide attempts, even after accounting for depression and hopelessness. Similarly, Heisel, Neufeld, and Flett () found that reasons for living and meaning in life were significant protective factors against suicidal ideation in a sample of 173 older adults.…”
Section: Shores: a Supported Mnemonicmentioning
confidence: 89%